Connection patterns distinguish 3 regions of human parietal cortex. - Rushworth, M; Behrens, T; Johansen-Berg, H (2006)
Three regions of the macaque inferior parietal lobule and adjacent lateral intraparietal sulcus (IPS) are distinguished by the relative strengths of their connections with the superior colliculus, parahippocampal gyrus, and ventral premotor cortex. It was hypothesized that connectivity information could therefore be used to identify similar areas in the human parietal cortex using diffusion-weighted imaging and probabilistic tractography. Unusually, the subcortical routes of the 3 projections have been reported in the macaque, so it was possible to compare not only the terminations of connections but also their course. The medial IPS had the highest probability of connection with the superior colliculus. The projection pathway resembled that connecting parietal cortex and superior colliculus in the macaque. The posterior angular gyrus and the adjacent superior occipital gyrus had a high probability of connection with the parahippocampal gyrus. The projection pathway resembled the macaque inferior longitudinal fascicle, which connects these areas. The ventral premotor cortex had a high probability of connection with the supramarginal gyrus and anterior IPS. The connection was mediated by the third branch of the superior longitudinal fascicle, which interconnects similar regions in the macaque. Human parietal areas have anatomical connections resembling those of functionally related macaque parietal areas.